2020
DOI: 10.1007/s00381-020-04851-9
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical dysplasia: etiology, epileptogenesis, classification, clinical presentation, imaging, and management

Abstract: Background Focal cortical dysplasia (FCD) is the most prevalent cause of intractable epilepsy in children. It was first described by Taylor et al. in 1971. In 2011, the International League against Epilepsy described an international consensus of classification for FCD. However, the exact mechanism causing this pathology remains unclear. The diagnosis and recognition of FCD increase with the advances in neuroradiology and electrophysiology. Focus of review In this paper, we discuss the literature regarding man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
(150 reference statements)
0
8
0
6
Order By: Relevance
“…The concept of FCD type Ⅲ can be defined as FCD type I adjacent to another principal lesion, such as hippocampal sclerosis (HS), low-grade developmental epilepsy-associated tumors (LDEATs), or vascular malformations [ 6 ]. The pathogenesis of FCD type Ⅲ is uncertain, because it is hard to tell whether the cortical dyslamination is primary or secondary [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of FCD type Ⅲ can be defined as FCD type I adjacent to another principal lesion, such as hippocampal sclerosis (HS), low-grade developmental epilepsy-associated tumors (LDEATs), or vascular malformations [ 6 ]. The pathogenesis of FCD type Ⅲ is uncertain, because it is hard to tell whether the cortical dyslamination is primary or secondary [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6] The complicated interaction between neurons, and imbalance in inhibitory and excitatory neurotransmitters are known mechanisms of epileptogenesis in FCD; with overexpression of AMPA and NMDA receptor subunits and loss of GABAergic neurons. [7,8] Many studies have recently suggested that focal epilepsy is not a limited to a speci c lesion, but results in alterations of the whole-brain network, due to the characteristic feature of the brain as a complex and interconnected system. [9,10] However, little is known about the structural connectivity or network in patients with FCD.…”
Section: Introductionmentioning
confidence: 99%
“…In 1971, Taylor first described focal cortical dysplasia (FCD), which is characterized by disordered neurons in white matter, dyslamination, and aberrant balloon cells, and can induce drug-resistant or intractable epilepsy. Approximately half (46.5%) of drug-resistant epileptic patients have pathologically confirmed abnormalities ( 1 , 2 ). The International League Against Epilepsy (ILAE) suggested the first international categorization of FCD in 2011 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…FCD type III comprises 4subgroups based on the pathophysiology of the accompanying lesions, specifically hippocampal sclerosis (FCD type IIIa), low-grade developmental epilepsy-associated tumors (LDEATs) (FCD type IIIb), vascular lesions (FCD type IIIc), and scar/hypoxic damage (FCD type IIId). ( 1 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%